Direct and Indirect effect of Knowledge Management Practices on Firm Innovation via Knowledge Application - Aleena Syed; Humna Sohail; Sarmad Ejaz; Hafiz Ahmed Ullah (International Review of Management and Marketing, 2020)
This study examines the relationship between knowledge management practices and firm innovation with the mediating effect of knowledge application. For the said purposes, data were collected from 140 firms that belong to the services sector. 600 questionnaires were distributed in the services sector by using the drop-off and pick up technique. The number of returned questionnaires was 545, but 45 questionnaires were rejected because they did not contain the required information. A simple random sampling technique is used for the data collection. The sampling technique followed the steps recommended for studies utilizing structural equational modeling (SEM). The data was entered into SPSS and AMOS for structural equation modeling. The empirical analysis shows that knowledge generation and knowledge diffusion have a significant positive effect on firm innovation while knowledge storage does not affect firm innovation. Moreover, knowledge application mediates the relationship between knowledge generation, knowledge storage, and firm innovation. While knowledge application does not play the mediation role between knowledge diffusion and innovation performance. Also, this study furnishes several future directions for academic scholars and participation. The limitations have also been discussed.